Optimization and analysis of bioethanol production from cassava starch hydrolysis - Liew, Emily Wan Teng (School of Engineering and Science, Curtin University Sarawak Malaysia, 2012)
Current ethanol production processes utilizing crops such as sugar cane and corn starch has been well established over the decade. Other crops such as cassava, is a potential candidate in producing ethanol. However, thermal processes are required to hydrolyze starch for the production of fermentable sugars. The processes are energy intensive and could lead to undesirable by-products generation. In this work, the hydrolysis of cassava starch is studied following an experimental design as a statistical problem solving approach. Central composite design (CCD) is used in order to select the most important variables from the simultaneous study on the effect and influence of operating conditions of bioreactor utilized, i.e. pH, temperature and substrate concentration, as well as to optimize the process of cassava starch hydrolysis. From the results obtained, it can be concluded that the cassava starch hydrolysis is enhanced by pH and temperature. Model validations show good agreement between experimental results and the predicted responses.